2013
DOI: 10.1371/journal.pone.0057375
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin Induces Release of Glucagon-Like Peptide-1 and Thereby Stimulates Insulin Secretion in Mice

Abstract: The uncarboxylated form (ucOC), but not the γ-carboxylated form (GlaOC), of the bone-derived protein osteocalcin stimulates insulin secretion and regulates energy metabolism in insulin target tissues. Glucagon-like peptide–1 (GLP-1) is an insulin secretagogue that is released from the gut in response to food intake. We have now found that Gprc6a, a putative ucOC receptor, is expressed in epithelial cells of the mouse small intestine as well as in STC-1 enteroendocrine cells. Secretion of GLP-1 by STC-1 cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
133
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 30 publications
4
133
1
2
Order By: Relevance
“…An identical volume of sterilized PBS was injected as a control. A glucose tolerance test was performed according to previous reports (55,56). Briefly, 2 min after injection of DPP4, a glucose solution (3 mg/g of body weight) was orally administered and blood glucose levels were measured at 0, 10, 30, 60, and 120 min using an OneTouch Ultravue device (Johnson & Johnson, New Brunswick, NJ).…”
Section: Discussionmentioning
confidence: 99%
“…An identical volume of sterilized PBS was injected as a control. A glucose tolerance test was performed according to previous reports (55,56). Briefly, 2 min after injection of DPP4, a glucose solution (3 mg/g of body weight) was orally administered and blood glucose levels were measured at 0, 10, 30, 60, and 120 min using an OneTouch Ultravue device (Johnson & Johnson, New Brunswick, NJ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, uncarboxylated form of OCN promotes insulin secretion to affect glucose metabolism by means of stimulating glucagons-like peptide-1 (GLP-1) [55]. OCN circulation can be attenuated by dietary phosphorus supplementation [56], implying functions of phosphorus in regulating OCN secretion and function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hepatic steatosis induced by a high-fat diet was completely recovered in mice treated with daily osteocalcin injection. Interestingly, the oral administration of osteocalcin also improved impaired glucose tolerance in vivo 38,39,41) . The ucOC via oral administration reached the small intestines, remained there for at least 24 h, and entered the general circulation.…”
Section: Glucose Metabolism Regulation By Osteocalcinmentioning
confidence: 98%
“…In addition to the direct effect of osteocalcin on insulin secretion, osteocalcin indirectly stimulates insulin expression and secretion by increasing the secretion of glucagon-like peptide-1 (GLP-1), which is an incretin released by intestinal endocrine cells. Mizokami et al demonstrated that the treatment with ucOC significantly increased GLP-1 expression in STC-1 enteroendocrine cells in vitro and that the administration of ucOC increased serum GLP-1 and insulin levels in mice 38,39) . These effects were potentiated by an inhibitor of dipeptidyl peptidase-4 and blocked by a GLP-1 receptor antagonist, suggesting that ucOC increases insulin secretion by enhancing GLP-1 secretion from intestinal endocrine cells.…”
Section: Glucose Metabolism Regulation By Osteocalcinmentioning
confidence: 99%